Dive into algorithms : a pythonic adventure for the intrepid beginner - Tuckfield, Bradford (No Starch Press, 2021)
"An introduction to algorithms for beginning coders that teaches readers a variety of common computer science algorithms, such as searching and sorting and optimization, as well as newer algorithms like those used in machine learning"--